Trade finance risk : documentary fraud and money laundering - Palmer, Howard (London : Euromoney Books, 2001)
Trade Finance Risk is a detailed yet practical guide to the detection and mitigation of the risks at the core of the international banking business. It draws on the extensive experience of the author as an expert trade finance practitioner. It is an essential and up-to-date guide to dealing with the scams that can be hidden by organised criminal groups. It also explains how to avoid becoming a victim of fraud and money laundering, something that every banker needs to understand.
rpm 30/06/14
Loan
Keywords: Fraud -- Great Britain; White collar crimes -- Great Britain; Money laundering -- Great Britain..